Is training for informal caregivers and their older persons helpful? A systematic review. (July 2019) - Aksoydan, Emine; Aytar, Aydan; Blazeviciene, Aurelija; van Bruchem - Visser, Rozemarijn L.; Vaskelyte, Alina; Mattace-Raso, Francesco; Acar, Sema; Altintas, Atahan; Akgun-Citak, Ebru; Attepe-Ozden, Seda; Baskici, Cigdem; Kav, Sultan; et al.
Highlights: Informal caregivers play a key role in nursing for older persons. Anxiety, depression, and loneliness are common problems in informal caregivers. Caregiver training can improve the patient's quality of life while reducing care costs. At the same time, support interventions for caregivers can reduce caregivers' stress. Abstract: Background: The steady increase in the number of people suffering from chronic diseases and increasing life expectancy raises new demands on health care. At the same time, the need for informal caregivers is increasing. This study aims to perform a systematic review of the methodologies used to identify effect of different types of training on informal caregivers and their older persons. Methods: MEDLINE (PubMed), CINAHL and Ovid were searched from December 2016 and April 2017. The following keywords were used; "informal caregiver", "training" "elderly", older persons". Identified publications were screened by using the following inclusion criteria; systematic reviews, randomized controlled trials, prospective cohort and multicentre studies, English language full text journals, samples or interventions that included caregivers of older persons and published in last 10 years. Results: Twenty four studies (12 randomised control trials, 8 intervention studies and 4 systematic reviews) were included. Most of the randomized controlled trials involved both caregivers and elderly. Pretests and post-tests were used in intervention studies (5 out of the 8 studies). ICT-based, psychosocial interventions on family caregivers' education program for caregivers were applied. Caregivers following a supportive educative learning had a significantly better quality of life. Conclusions: The findings of this systematic review suggest that support interventions for caregivers can be effective in reducing caregivers' stress, with a consequent improvement of the quality of care. However, results are based on relatively small studies, reporting somewhat controversial findings supporting the need to perform further research in this field.